Determinant of Poverty Level in West Kutai Regency, Indonesia - Akin, Emanuel (Universitas Muhammdaiyah Surakarta, 2014)
This research is Library Research by using secondary data obtained and seeks to determine and analyze the factors that affect poverty in West Kutai regency, the analysis tool is use Path Analysis. Conclusion of the research results are as follows: (1) Economic Growth, Private Investment Growth (PMA), Labor, and the Growth of Government expenditure jointly direct and significant effect on the Human Development Index (HDI) in West Kutai regency, (2 ) Workforce dominant influence on the Human Development Index (HDI) in West Kutai regency, (3) Economic Growth, Private Investment Growth (PMA), Labor, and Output Growth Government jointly direct and significant effect on the amount of Poor Population in West Kutai regency, (4) Workforce dominant influence on the amount of Poor People in West Kutai regency, (5) Economic Growth, Private Investment Growth (PMA), Labor, and the Growth of Government influence indirectly through the Human Development Index (HDI) of the total poor population in West Kutai.